2015
DOI: 10.1128/aac.04181-14
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Artemether-Lumefantrine and Dihydroartemisinin-Piperaquine for Treatment of Uncomplicated Malaria in Children in Zaire and Uíge Provinces, Angola

Abstract: The development of resistance to antimalarials is a major challenge for global malaria control. Artemisinin-based combination therapies, the newest class of antimalarials, are used worldwide but there have been reports of artemisinin resistance in Southeast Asia. In February through May 2013, we conducted open-label, nonrandomized therapeutic efficacy studies of artemetherlumefantrine (AL) and dihydroartemisinin-piperaquine (DP) in Zaire and Uíge Provinces in northern Angola. The parasitological and clinical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 34 publications
6
77
0
Order By: Relevance
“…Some studies in Africa have observed a low frequency of other mutations, some of which are found in the propeller domain, in parasites from Africa (38)(39)(40). To date, many of the therapeutic efficacy studies conducted in Africa have indicated that artemisinin-based combination therapies are still efficacious (21,41,42). Therefore, the role of the novel African K13 mutations in artemisinin resistance, if any, is still to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies in Africa have observed a low frequency of other mutations, some of which are found in the propeller domain, in parasites from Africa (38)(39)(40). To date, many of the therapeutic efficacy studies conducted in Africa have indicated that artemisinin-based combination therapies are still efficacious (21,41,42). Therefore, the role of the novel African K13 mutations in artemisinin resistance, if any, is still to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Samples used in this study were collected prior to treatment. Samples from Ghana were collected between 1999 and 2010, samples from Tanzania in 2011, and samples from Angola in 2013 [30]. Electronic supplementary material, figure S1, shows study locations and malaria prevalence.…”
Section: (B) Sample Collection and Processingmentioning
confidence: 99%
“…The second source of data is a set of 24 treatment failures from a 2013 in vivo therapeutic efficacy study of AL and dihydroartemisin-piperaquine (DP) in children with uncomplicated P. falciparum malaria in Zaire and Uíge provinces in Angola (14). There were 24 late treatment failures observed in three of the study arms: AL in Zaire, AL in Uíge, and DP in Zaire.…”
Section: Methodsmentioning
confidence: 99%
“…Samples from day 0 and the day of treatment failure for each treatment failure had been genotyped using seven neutral microsatellites. In addition to the previously published microsatellite data from the treatment failures, all remaining day-0 samples from all 398 enrolled patients in both Angolan sites using six of the seven original loci were analyzed, following the methods from the original paper (14).…”
Section: Methodsmentioning
confidence: 99%